Exploring managers’ response to a quality and safety leadership intervention: findings from a multiple case study in Norwegian nursing homes and homecare services - Eline Ree; Terese Johannessen; Siri Wiig; Ingunn Aase; Roland Bal (BMJ Open Quality)
Background Improvement interventions would be easier to treat if they were stable and uninfluenced by their environment, but in practice, contextual factors may create difficulties in implementing and sustaining changes. Managers of healthcare organisations play an important role in quality and safety improvement. We need more research in the nursing home and homecare settings to support managers in their quality and safety improvement work. The aim of this study was to explore managers’ response to a leadership intervention on quality and safety improvement.Methods This study reports findings from the SAFE-LEAD intervention undertaken from April 2018 to March 2019. The research design was a multiple case study of two nursing homes and two homecare services in four municipalities in Norway. We used a combination of qualitative methods including interviews, workshops, observations, site visits and document analysis in our data collection that took place over a 1-year period.Results Management continuity was key for the implementation process of the quality and safety leadership intervention. In the units where stable management teams were in place, the intervention was more rooted in the units, and changes in quality and safety practice occurred. The intervention served as an arena for managers to work with quality and safety improvement. We found that the workshops and use of the leadership guide contributed to a common understanding and commitment to quality and safety improvement among the managers.Conclusions This is a longitudinal study of managers’ response to a leadership intervention targeted to improve quality and safety work in nursing home and homecare settings. Our research demonstrates how the mechanisms of stable management and established structures are crucial for quality and safety improvement activities. Management continuity is key for participating in interventions and for using the leadership guide in quality and safety work.